(untitled) (Research, Society and Development, 2022)
Prenatal care (PC) is an important tool in maintaining the health of pregnant woman and fetus, being important in reducing deaths and the appearance of complications. For this, the Ministry of Health (MH) instituted the Programa de Humanização no Pré-Natal e Nascimento (PHPN), aiming to standardize care and propose a link between PC and childbirth services. The objective of the study was to relate the level of adequacy of PC with the occurrence of adverse events during pregnancy in the state of Minas Gerais. It is a documentary, descriptive, exploratory, cross-sectional and retrospective study, of quantitative nature. Data were extracted from the Sistema de Informação sobre Nascidos Vivos (SINASC), and included pregnant women who underwent prenatal care, in the period between 2015-2020. Data were processed using SPSS version 25.0. We opted for the chi-square test for bivariate analysis (p<0.05). The results showed that most women performed an adequate PC. Regarding the characteristics of the pregnancies, most babies did not present congenital anomalies (95.7%), had a gestation period of 37 to 41 weeks (81.3%), with adequate birth weight (86.9%) and with good APGAR results at the 1st (86.4%) and 5th minute (95.4%). According to our data, there is a high rate of coverage of PC in Minas Gerais, considering the minimum criteria of the Ministry of Health. However, the presence of risk factors correlates to worse postnatal outcomes. It is extremely important to identify risk factors early on the pregnancy, aiming at a better PC result.